COMPUTATIONAL PROGRAM TO DETERMINE THE AGRICULTURAL PRODUCTS EQUILIBRIUM MOISTURE - Teles Junior, C. G. S.; Vilela, M. O. (Revista Brasileira de Engenharia de Biossistemas, 2020)
The equilibrium moisture is an important post-harvest concept, since it is directly related to the grains drying and storage. The aim of this study was to develop a computational tool to help calculate the equilibrium moisture of different agricultural products. The software for the determination of agricultural products equilibrium moisture (UeGrão), was developed using the C# programming language in the Microsoft Visual C# 2010 Express Integrated Development Environment. The software graphical interface is basically divided into three windows, the first is an initial window, from which the main window is opened and window 3 which is an information window, bringing a more detailed presentation of the developed software. The developed software is easy to use and intuitive for the user, constituting a useful tool that can be used by researchers, students and producers to evaluate the conditions of their stored products.